Comparative foliar anatomical study of six different varieties of Piper betle L. - Begam, K. Mydeen Fathima; Ravichandran, P.; Manimekalai, V. (Current Botany, 2023)
The present investigation on a few selected cultivars of Piper betle L. was undertaken mainly to understand the anatomy and tissue components of the stem, leaves and petiole. This was accomplished by using basic anatomy techniques such as free hand and microtome sectioning. The varieties selected were: HY1, HY2, JB, KB, LV and SG. Major aspects of the present inquiry were - macro morphology, anatomy and histochemistry. The main focus of the study was on the internal structure of leaves and petioles to understand the role of specialised cells like enlarged hypodermal cells and mucilage cavities in retaining moisture and thereby preserving the shelf life of harvested leaves.